Pengaruh Risiko Pembiayaan Murabahah, Mudharabah dan Risiko Likuiditas Terhadap Profitabilitas pada Bank Syariah (Studi pada BCA Syariah periode 2015-2022) - Siva Nurhaliza (TSARWAH, 2023)
The purpose of this research is to determine the effect of murabahah, mudharabah, and liquidity risk risks on the level of profitability as seen from ROA (Return On Assets) at BCA Syariah. In this study using quantitative methods and using secondary data obtained from BCA Syariah quarterly financial reports for the 2015-2022 period published by the OJK. The population of this study was 31 with a saturated sampling technique, so a sample of 31 samples. Data analysis techniques in this study used multiple linear regression tests, and used hypothesis testing in the form of T tests, F tests, and coefficient of determination tests (R2). The results of this study indicate that murabahah financing risk (NPF murabahah), mudharabah financing risk (NPF mudharabah), and liquidity risk (FDR) do not significantly influence profitability (ROA) at BCA Syariah, either partially or simultaneously.